Machine learning approaches towards identifying inhibitors for plasmodium falciparum cGMP-dependent protein kinase. - Thibaud, Jessica Leigh (Stellenbosch : Stellenbosch University, 2025)
Thesis (PhD)--Stellenbosch University, 2025.